Life insurance premium and Covid-19 - Glušac Danijela (Trendovi u Poslovanju)
Insurance, as a source of society's aspirations, represents the association of all those who are exposed to the same danger. The coronavirus pandemic has affected various aspects of life, including the insurance industry. Life insurance is one of the types of insurance where the obligations of insurance companies to policyholders have increased during the coronavirus pandemic. The paper analyzes the normative complex of the insurance premium with the specifics and characteristics of this topic. We consider it important to comprehensively explain the premium as an essential element of the life insurance contract. The analysis includes how the coronavirus pandemic is affecting life insurance premiums. This period of change could be a turning point and lead to transformational changes in the life insurance industry. Those who are able to adapt quickly to changes in the environment, who prioritize the insurance consumer and who see this crisis as an opportunity to start from scratch and fundamentally rethink the way they do business will quickly find their place when things calm down.